Meningkatkan Pemahaman Fakta Melalui Penerapan Model Pembelajaran Kooperatif Tipe Examples Non Examples pada Mata Pelajaran Sosiologi di Kelas XI IPS 1 SMAN 1 Solok Selatan - Aldi Fradana; Firman Firman; Rusdinal Rusdinal (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
This research is motivated by the author's interest in seeing the lack of understanding of students about the facts explained by the teacher in the subject of Sociology in class XI IPS 1 SMAN 1 Solok Selatan. Based on this, researchers are interested in conducting research with efforts to improve understanding of facts through the application of the Examples Non Examples cooperative learning model in Sociology subjects in class XI IPS 1 SMAN 1 Solok Selatan. The theory used in this study is the theory of learning discovery from Jerome Bruner, namely by constructing the information that is owned and only obtained then someone will be able to provide the right facts to explain the concept because of the construction it produces. With the support of the Examples Non Examples cooperative learning model in this study, understanding students' facts about the information they get will be even better. The results of this study reveal that using the Examples Non Examples model can make students' understanding of facts more improved. This is evident that there has always been a better improvement at each meeting. Not only on the results of observation, students' understanding also increases when given a case analysis problem.